Learning in Simulated Environments: A Comparison to Learning in a Physical Environments Using Video Data Analysis. (September 2017) - Alfred, Myrtede; Lee, Moris; Neyens, David M.; Gramopadhye, Anand K.
Few studies that have evaluated the efficacy of learning in simulated environments have also examined differences in the processes that learners in the simulated environments employed to arrive at the outcomes being measured. In this video analysis study, the researchers sought to understand whether there were differences in the construction process used by participants who learned to construct circuits using a 2D simulation, a 3D simulation, or a physical breadboard and whether these differences subsequently impacted several learning outcomes. The researchers systematically reviewed 30 videos (10 videos per condition) of participants' circuit construction to identify variations in their comprehension level and their construction procedures. The study found differences in the construction process, odds of successful construction, and construction time for participants in the three conditions that could be attributed to differences in fidelity. These findings provide valuable insights about how learning in simulated environments impact proficiency and learning and can help improve the design of simulated learning environments.